Drosophila von Hippel-Lindau Tumor Suppressor Gene Function in Epithelial Tubule Morphogenesis - Hsouna, Anita (American Society for Microbiology (ASM), 2010)
Mutations in the human von Hippel-Lindau (VHL) gene are the cause of VHL disease that displays multiple benign and malignant tumors. The VHL gene has been shown to regulate angiogenic potential and glycolic metabolism via its E3 ubiquitin ligase function against the alpha subunit of hypoxia-inducible factor (HIF-α). However, many HIF-independent functions of VHL have been identified. Recent evidence also indicates that the canonical function cannot fully explain the VHL mutant cell phenotypes, although it is still unclear how many of these noncanonical functions relate to the pathophysiological processes because of a lack of tractable genetic systems. Here, we report the first genomic mutant phenotype of Drosophila melanogaster VHL (dVHL) in the epithelial tubule network, the trachea, and show that dVHL regulates branch migration and lumen formation via its endocytic function. The endocytic function regulates the surface level of the chemotactic signaling receptor Breathless and promotes clearing of the lumen matrix during maturation of the tracheal tubes. Importantly, the regulatory function in tubular morphogenesis is conserved in the mammalian system, as conditional knockout of Vhl in mouse kidney also resulted in similar cell motility and lumen phenotypes.